2016
DOI: 10.1111/jfpp.13029
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolics and Antioxidant Capacity of Cocoa Pulp: Processing and Storage Study

Abstract: Cocoa pulp, the white mucilage that surrounds cocoa beans, is the main substrate in cocoa bean fermentation and is rich in macro-and micronutrients. Yet, the presence of phenolics and their antioxidant activity in cocoa pulp has not been explored. The objectives of this study were to quantify the total phenolics of cocoa pulp by using FolinCiocalteu assay and antioxidant activity by using Oxygen Radical Absorption Capacity (ORAC) assay as well as Cellular Antioxidant Activity (CAA) assay. The effect of single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…After 5 weeks of storage at 37 °C, metal ions can help retain approximately 6% more TPC as compared to control sample. Significant reduction in TPC during storage was reported by Endraiyani (). The addition of Ca 2+ seemed to show little effects on retention of polyphenolics in Muscadine juice (Talcott, Brenes, Pires, & Del Pozo‐Insfran, ).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…After 5 weeks of storage at 37 °C, metal ions can help retain approximately 6% more TPC as compared to control sample. Significant reduction in TPC during storage was reported by Endraiyani (). The addition of Ca 2+ seemed to show little effects on retention of polyphenolics in Muscadine juice (Talcott, Brenes, Pires, & Del Pozo‐Insfran, ).…”
Section: Resultsmentioning
confidence: 73%
“…After 5 weeks of storage at 37 8C, metal ions can help retain approximately 6% more TPC as compared to control sample. Significant reduction in TPC during storage was reported byEndraiyani (2011).…”
mentioning
confidence: 89%
“…Under the LBOA conditions, the decrease in the total phenolic content could be delayed most, followed by the LB and PPWB conditions. Endraiyani, Ludescher, DI, and Karwe () have studied the change in the total phenolic content of cocoa pulp during storage and found that the storage time had a significant effect on the content. The content decreased along with storage time.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study is to better investigate the cyto-histological characteristics of cocoa seeds related to their composition in secondary metabolites, such as polyphenol and tocopherols. To our knowledge, there are in literature many data about the histological characterization of cocoa seeds (Martini et al, 2008;Elwers et al, 2010), as well as biochemical studies about its phenolics content and antioxidant capacity (Aprotosoaie et al, 2016;Endraiyani et al, 2016;Wang et al, 2016), but a specific localization of the phytochemicals in the different structures of seed and fruit has not been carried out yet. Metabolite localization was focused until now in the cotyledon structure, but, as previous described, also other structure of seed and fruit are important for the flavour development and nutritional characteristics.…”
Section: Introductionmentioning
confidence: 99%